2020
DOI: 10.3390/ijerph17082715
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Growth of Sulfate-Reducing Bacteria with Bioleaching Acidophiles for Bioremediation of Heap Bioleaching Residue

Abstract: Mining waste rocks containing sulfide minerals naturally provide the habitat for ironand sulfur-oxidizing microbes, and they accelerate the generation of acid mine drainage (AMD) by promoting the oxidation of sulfide minerals. Sulfate-reducing bacteria (SRB) are sometimes employed to treat the AMD solution by microbial-induced metal sulfide precipitation. It was attempted for the first time to grow SRB directly in the pyritic heap bioleaching residue to compete with the local ironand sulfur-oxidizing microbes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…An interesting aspect is the increase in sulfite concentration. The metabolism of bioleaching bacteria should lead to the oxidation of energy substrates to sulfates [ 56 , 57 ]. It can, therefore, be suggested that the samples were still a reaction–culture environment.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting aspect is the increase in sulfite concentration. The metabolism of bioleaching bacteria should lead to the oxidation of energy substrates to sulfates [ 56 , 57 ]. It can, therefore, be suggested that the samples were still a reaction–culture environment.…”
Section: Resultsmentioning
confidence: 99%
“…In Arizona, there are potential mechanisms in which sulfates may enter rainwater harvesting systems. As sulfates are the main electron acceptor for SRB in anaerobic environments, environments containing them provide a natural habitat for their growth (Phyo et al, 2020 ). There exist several pathways for potential sulfate contact with water sources in residential settings.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examined bioleaching using the iron-oxidising bacteria of Acidithiobacillus ferrooxidans (Brinza et al, 2021). However, the induction of exogenous or exotic bacteria in the bioleaching process caused competition with local bacteria, thereby resulting in negative effects (Phyo et al, 2020). They influenced the function of local ecosystems due to changes in local microorganism populations, and the level of biogeochemical cycles (Moore et al, 2022).…”
Section: Introductionmentioning
confidence: 99%